Exploring Disease Manifestations and Influencing Factors in Acute and Chronic Hepatitis B - Sam, Napoleon Bellua; Ofosu, Abena Serwaa; Majeed, Saeed Folorunsho (European Scientific Journal, ESJ, 2024)
Scope and Aims: The investigation of disease manifestations and influencing factors in both acute hepatitis B (AHB) and chronic hepatitis B (CHB) remains limited, with varying results. This study aimed to explore the factors influencing AHB and CHB and their disease manifestations within a Ghanaian population, with the goal of developing a control strategy. Methods: A retrospective study was conducted on 569 admitted hepatitis B cases. Demographic data and disease manifestations were compared between AHB and CHB patients. Logistic regression and correlation analyses were employed to identify the factors influencing the progression of the disease. Results: Significant differences were observed between AHB and CHB patients in terms of median age and hospitalization duration. Variations in age, gender, education level, and occupational distributions were statistically significant (P < 0.05) between the two groups. Symptoms such as fever, nausea, polydipsia, palpitation, anicteric presentation, anorexia, and itching were less common in CHB patients (P < 0.05), while abdominal pain, jaundice, and enlarged liver were more frequent (P < 0.05). CHB patients exhibited significantly higher levels of aspartate aminotransferase, viral load, bilirubin, prothrombin time, partial thromboplastin time, HBeAg, albumin, abdominal ultrasound findings, and globin (P < 0.05), while HBsAg and liver function test levels were significantly lower (P < 0.05) in CHB patients compared to AHB patients. Logistic regression identified age, gender, occupation, education level, and hospitalization duration as significant influencing factors. Conclusion: Males and the adult population represented a higher proportion of CHB patients, with a significant association between CHB and elevated clinical and laboratory characteristics. Age, gender, occupation, education level, and hospitalization duration were established as key influencing factors in the progression of hepatitis B.